2018
DOI: 10.1101/464305
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Simultaneous mesoscopic Ca2+ imaging and fMRI: Neuroimaging spanning spatiotemporal scales

Abstract: To achieve a more comprehensive understanding of brain function requires simultaneous measurement of activity across a range of spatiotemporal scales. However, the appropriate tools to perform such studies are largely unavailable. Here, we present a novel approach for concurrent wide-field optical and functional magnetic resonance imaging (fMRI). By merging these two modalities, we are for the first time able to simultaneously acquire whole-brain blood-oxygen-leveldependent and whole-cortex calcium-sensitive f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…LocaNMF differs in the introduction of an atlas to localize the components; this directly enables across-subject comparisons and assigns region labels to the components (while still allowing the spatial footprints of the extracted components to shift slightly from brain to brain), which can be helpful for downstream analyses. Furthermore, recent studies have shown that the spatial and temporal activity recorded from WFCI and fMRI during spontaneous activity show considerable similarities 3,36 . Given these conceptual similarities, we believe there are opportunities to adapt the methods we introduced here to fMRI or other three-dimensional (3D) functional imaging modalities 37,38 , while using a 3D atlas of brain regions to aid in localization of the extracted demixed components.…”
Section: Resultsmentioning
confidence: 99%
“…LocaNMF differs in the introduction of an atlas to localize the components; this directly enables across-subject comparisons and assigns region labels to the components (while still allowing the spatial footprints of the extracted components to shift slightly from brain to brain), which can be helpful for downstream analyses. Furthermore, recent studies have shown that the spatial and temporal activity recorded from WFCI and fMRI during spontaneous activity show considerable similarities 3,36 . Given these conceptual similarities, we believe there are opportunities to adapt the methods we introduced here to fMRI or other three-dimensional (3D) functional imaging modalities 37,38 , while using a 3D atlas of brain regions to aid in localization of the extracted demixed components.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, these studies have been carried out in the context of a larger collaboration to relate neural activity across a broad range of spatiotemporal scales. We have also established an approach for carrying out mesoscopic calcium imaging simultaneously with functional magnetic resonance imaging (fMRI) 16 . This method will enable us to link the activity of targeted cells to brain-wide activity measured by blood oxygenation level-dependent (BOLD) signaling in mice as well as relating such activity to analogous fMRI studies in humans.…”
Section: Discussionmentioning
confidence: 99%
“…For the individualized functional parcellation, we applied a multi-graph k-way spectral clustering algorithm, as is described in greater detail elsewhere 16 . For each mouse, the parcellation was determined using widefield-only imaging data collected prior to microprism implantation.…”
Section: Parcellation Of Widefield Imaging Datamentioning
confidence: 99%
See 1 more Smart Citation
“…LocaNMF differs in the introduction of an atlas to localize the components; this directly enables across-subject comparisons and assigns region labels to the components (while still allowing the spatial footprints of the extracted components to shift slightly from brain to brain), which can be helpful for downstream analyses. Furthermore, recent studies have shown that the spatial and temporal activity recorded from WFCI and fMRI during spontaneous activity show considerable similarities [3,36]. Given these conceptual similarities, we believe there are opportunities to adapt the methods we introduced here to fMRI or other three-dimensional (3D) functional…”
Section: Discussionmentioning
confidence: 97%